Crises in Schools and Crısis Management Skills of Principals - Şahin, Münir (Science Insights Education Frontiers, 2026)
This study aims to explore the crisis management skills that school principals need in diverse crisis contexts. This is qualitative research which seeks to synthesize contemporary knowledge and perspectives in related documents and the literature concerning the crisis management competencies of school principals. Adopting a document analysis and literature review approach, the study focuses on both national and international academic sources published between 2015 and 2025. The analysis identifies the major types of crises, natural disasters, technological disruptions, human-related incidents, social and political tensions, and health emergencies, and evaluates the competencies principals must demonstrate, including situational awareness, communication, rapid decision-making, resilience, and collaborative leadership. Findings emphasize that effective crisis management extends beyond technical preparedness and requires psychosocial awareness, ethical sensitivity, and empathic leadership. The study also underscores the importance of principals addressing teacher isolation and burnout during crises, while fostering organizational resilience and stakeholder trust. Ultimately, the research highlights the urgent need for policy-level support and practice-based training programs that will enhance principals’ capacity to act as crisis leaders in increasingly complex educational environments.